4-phenylbutyrate Mitigates Fluoride-Induced Cytotoxicity in ALC Cells - Suzuki, Maiko; Everett, Eric T.; Whitford, Gary M.; Bartlett, John D. (Frontiers in Physiology, 2017)
Chronic fluoride over-exposure during pre-eruptive enamel development can cause dental fluorosis. Severe dental fluorosis is characterized by porous, soft enamel that is vulnerable to erosion and decay. The prevalence of dental fluorosis among the population in the USA, India and China is increasing. Other than avoiding excessive intake, treatments to prevent dental fluorosis remain unknown. We previously reported that high-dose fluoride induces endoplasmic reticulum (ER) stress and oxidative stress in ameloblasts. Cell stress induces gene repression, mitochondrial damage and apoptosis. An aromatic fatty acid, 4-phenylbutyrate (4PBA) is a chemical chaperone that interacts with misfolded proteins to prevent ER stress. We hypothesized that 4PBA ameliorates fluoride-induced ER stress in ameloblasts. To determine whether 4PBA protects ameloblasts from fluoride toxicity, we analyzed gene expression of Tgf-β1, Bcl2/Bax ratio and cytochrome-c release in vitro. In vivo, we measured fluorosis levels, enamel hardness and fluoride concentration. Fluoride treated Ameloblast-lineage cells (ALC) had decreased Tgf-β1 expression and this was reversed by 4PBA treatment. The anti-apoptotic Blc2/Bax ratio was significantly increased in ALC cells treated with fluoride/4PBA compared to fluoride treatment alone. Fluoride treatment induced cytochrome-c release from mitochondria into the cytosol and this was inhibited by 4PBA treatment. These results suggest that 4PBA mitigates fluoride-induced gene suppression, apoptosis and mitochondrial damage in vitro. In vivo, C57BL/6J mice were provided fluoridated water for six weeks with either fluoride free control-chow or 4PBA-containing chow (7g/kg 4PBA). With few exceptions, enamel microhardness, fluorosis levels, and fluoride concentrations of bone and urine did not differ significantly between fluoride treated animals fed with control-chow or 4PBA-chow. Although 4PBA mitigated high-dose fluoride toxicity in vitro, a diet rich in 4PBA did not attenuate dental fluorosis in rodents. Perhaps, not enough intact 4PBA reaches the rodent ameloblasts necessary to reverse the effects of fluoride toxicity. Further studies will be required to optimize protocols for 4PBA administration in vivo in order to evaluate the effect of 4PBA on dental fluorosis.